Case Series: Extracorporeal Shockwave Myocardial Revascularization Therapy Improves Ischemic Response, Functional Capacity, and Quality of Life in Indicated CABG-Stable Angina Pectoris Patients - Akbar, Mohammad Rizki; Adiputro, Dwi Laksono; Tiksnadi, Badai Bhatara; Soeriadi, Erwin Affandi; Hasan, Melawati; Muttaqien, Fauzan; Raharjo, Pradana Pratomo; Nurazizah, Eliza; Tarsidin, Najmi Fauzan (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Extracorporeal shockwave myocardial revascularization (ESMR) is included in the guidelines only for refractory angina pectoris patients with no option for invasive revascularization. We intend to report a case series with ESMR therapy in indicated coronary artery bypass grafting-stable angina pectoris (CABG-SAP) patients which refuse the surgery, irrespective of angina symptoms. Methods: We review medical records of SAP patients admitted to ESMR therapy in Dr. Hasan Sadikin General Hospital, Bandung, Indonesia from January 2018 to December 2019. Recorded variables at baseline and after therapy extracted including: (1) ischemic response, double product, and (2) functional capacity measured as metabolic equivalent (METs) using treadmill test; (3) six-minute walking test distance achieved; and (4) quality of life using SF-36 Questionnaire. Results: Four indicated CABG-SAP patients from 50 to 75 years old were included in this study. At baseline, one patient is CCS class I and two patients are CCS class II with SDS ranging from 3 to 17. Ischemic response improved in all patients. The double product improved in Patient 1 9600 to 14872 mmHg*bpm, Patient 2 9460 to 10640 mmHg*bpm, and Patient 4 17220 to 20480 mmHg*bpm. The Functional capacity improved in Patient 1 8.07 to 8.91 METs, Patient 2 1.91 to 4.01 METs, Patient 3 3.45 to 6.39 METs, and Patient 4 3.9 to 4.43 METs. The six-minute walking distance improved in Patient 1 540 to 570 m and Patient 2 345 to 405 m. The CCS class, Bodily Pain, and General Health domain scores improved in all patients. Conclusion: ESMR therapy might be beneficial for indicated CABG-SAP patient to improve ischemic response, functional capacity, and physical component of quality of life.